How does digital inclusive finance influence non-agricultural employment among the rural labor force? ——Evidence from micro-data in China - Yan Wang; Yin Qi; Yi Li (Heliyon, 2024)
In the context of the integration and development of inclusive finance and digital technology, exploring the relationship between digital inclusive finance and non-farm employment of rural laborers is of great significance in promoting rural economic development and realizing common prosperity for all. Based on data from the 2018 and 2020 China Family Tracking Survey (CFPS) and Peking University's Digital Financial Inclusion Index, this paper investigates the impact of digital inclusive finance on the non-farm employment of rural labor and its transmission mechanism. The results of the study show that both digital inclusive finance and its sub-dimensions can promote the non-farm employment of rural laborers, and have stronger inclusion and inclusiveness compared with traditional inclusive finance. Mechanism analysis shows that both Internet use and social trust can positively moderate the relationship between digital inclusive finance and non-farm employment of rural laborers, and that digital inclusive finance can promote non-farm employment of rural laborers by alleviating financing constraints and enhancing risk preferences. Further heterogeneity analysis shows that digital inclusive finance promotes employed non-farm employment more significantly than entrepreneurial non-farm employment, and on this basis, there are also differences for different employment groups and different regions. The findings of this study aim to provide theoretical reference and support for relevant departments to formulate policies to realize higher quality full employment of rural labor.